An investigation of the physiological and pathological role of uncoupling proteins - Manzke, Lars (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
Uncoupling proteins (UCPs) are found in numerous different tissues and have been associated with many physiological and pathological conditions. After decades of research on uncoupling proteins, there is still only a modest understanding of how the uncoupling protein function is regulated. Furthermore, the functions of the "new" uncoupling proteins 2 and 3 are still unknown, although there is some evidence that they catalyze a proton leak similar to UCPl. The present work characterizes the role of uncoupling proteins 1, 2 and 3 in physiological and pathological models.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.